The confinement of phonon propagation in TiAlN/Ag multilayer coatings with anomalously low heat conductivity - Kovalev, Anatoly I.; Wainstein, D. L.; Rashkovskiy, A. Y.; Gago, R.; Soldera, F.; Endrino, José L. (American Institute of Physics (AIP), 2016)
TiAlN/Ag multilayer coatings with a different number of bilayers and thicknesses of individual layers were fabricated by DC magnetron co-sputtering. Thermal conductivity was measured in dependence of Ag layer thickness. It was found anomalous low thermal conductivity of silver comparing to TiAlN and Ag bulk standards and TiAlN/TiN multilayers. The physical nature of such thermal barrier properties of the multilayer coatings was explained on the basis of reflection electron energy loss spectroscopy. The analysis shows that nanostructuring of the coating decreases the density of states and velocity of acoustic phonons propagation. At the same time, multiphonon channels of heat propagation degenerate. These results demonstrate that metal-dielectric interfaces in TiAlN/Ag coatings are insurmountable obstacles for acoustic phonons propagation.